Feed technologies and efficiency in cow-calf systems - Rosa, Yago Machado da (2022)
This study was performed to evaluate the efficiency index of cow-calf systems, based on different feed technologies commonly employed in the Rio Grande do Sul state, southern Brazil. Hence, the efficiency of 35 cow-calf herds was evaluated by Data Envelopment Analysis (DEA). Data was collected by online survey and in-depth interviews, as well as data registers from the cow-calf systems, located in 31 municipalities. The analyzed indicators included rates of mortality, pregnancy, birth, and productivity. The feed technologies evaluated were the use of cultivated pastures during winter and summer, supplementation during winter and summer, creep feeding, deferral of natural pasture, use of grazing systems, and employee’s capacitation. Approximately 80% of the evaluated farms showed low-to-medium Efficiency Index (EI; up to 0.79 in a scale of 0 to 1), 13% presented high EI, and only 7% had very high EI (above 0.95). The use of cultivated pastures with the inclusion of protein supplementation and employees’ capacitation were highlighted as the main practices to increase efficiency of cow-calf systems in Rio Grande do Sul. The technologies identified as most impactful raise the EI of production systems from low to medium. Our results assist in decision-making in the use of feed technologies, pointing out a direction for the use of technologies that make breeding systems more efficient from a productive point of view.